Ethnobotanical, phytochemistry, and pharmacological property of Waltheria Indica Linn - C Nirmala; M Sridevi (SpringerOpen, 2021)
Abstract Background In modern therapeutics, various human pathological disturbances were treated with the plant-based products. Waltheria indica Linn, a perennial herb, was commonly used in traditional medicine worldwide against various ailments such as cough, dysentery, diarrhea, bladder disorder, hemoptysis, inflammations, neuralgia, wounds, and ulcers. Main body The shrub was majorly distributed in tropical, subtropical regions and exists in many distinct local forms. Both the crude extracts and purified compounds from the whole plant and its parts showed wide pharmacological properties like antioxidant, analgesic, sedative, anti-bacterial, anti-fungal, and anti-parasitic. The phytochemical profile and traditional usage highlight the potency of the plant in the treatment of microbial infections and inflammatory diseases. Yet, additional studies are required for the confirmations of its traditional uses against other diseases. More detailed understanding of anti-cataract, anti-diabetics, asthma, anemia, and anti-cancer mechanism has to be explored. Though many research articles on the proposed plant are available, there has been a rising concern in the therapeutic property, especially on the alkaloids and flavonoids from this plant for drug design. Conclusion This article aims in a systematic and updated review on distribution, botany, traditional uses, phytocompounds, and relevant biological activities from each part of the plant. The information was collected from databases like PubMed, ScienceDirect, Web of Science, Google Scholar, books, dissertation, and reports via academic libraries that included more than 100 articles published since 1937. This ethnopharmacological study of the plant may create new insight into drug discovery to develop important novel leads against various biological targets.